Xerostomia – An Unknown Oral Manifestation in AAA Syndrome - Deepali Agrawal; Ravikiran Ongole (Indian Journal of Forensic Medicine & Toxicology, 2021)
Background: The triple A syndrome (AAAS), also termed Allgrove syndrome (AS), is a very rare chromosomerecessive disorder that was 1st identified in 1978 by Jeremy Allgrove and colleagues in 2 unrelated siblings.In most cases, there is no associated family history. The syndrome comprises of Achalasia, Addisonianismand Alacrimia. It has an estimated prevalence of 1 per 1,000,000 individuals. About 200 cases have beenreported worldwide as of date, showing a great variability in severity as well as in clinical manifestations.Consistent oral findings could be noticed such as high arched palate, oral pigmentation, fissured or atrophictongue, and xerostomiaCase report: We report the case of a 25-year-old girl who presented with Triple A Syndrome with allcharacteristic clinical features.Conclusion: The aim of this case report is to highlight the dental involvement in Allgrove syndrome. Inaddition, we aim to emphasize the need for the oral physician to accurately diagnose the condition, managethe oral manifestations, and to collaborate with other dental specialists to provide optimum dental care tothese patients.